Impact of Group Clinical Supervision on Patient Education Process: A Comprehensive Assessment of Patients, Staff, and Organization Dimensions - Afsaneh Jafari Moghadam; Fatemeh Heshmati Nabavi; Atefeh Behboudifar; Seyed Reza Mazloom; Farhad Heydarian (Mashhad University of Medical Sciences, 2018)
Background: The most important barriers to patient education are nurses' poor motivation and training, and poor quality of managerial supervision. Clinical supervision could be a powerful tool for overcoming these barriers. However, the associated patient, staff, and organization-related outcomes still require further research. Aim: The present study aimed to evaluate the patient-, staff-, and organization-related outcomes of group clinical supervision with the goal of improving patient education. Method: This quasi-experimental study was conducted on 35 nurses and mothers of 94 children admitted to the surgery and nephrology wards of Dr. Sheikh Hospital, Mashhad, Iran, in 2016. A 3-month clinical supervision program consisting of support, education, feedback, and facilitation stages was implemented with the assistance of education facilitators. The data were collected using the questionnaire of patient's satisfaction with nurses' education, Herzberg's job motivation questionnaire, and the checklists of nurses' education performance and quality of education documentation. Data analysis was performed by Mann-Whitney U test, Fisher's exact test, and independent-t test in SPSS, version 14. Results: The mean ages of the nurses, patients, and mothers were 30.3±6.7, 5.2±3.8, and 32.2±6.2, respectively. Mann-Whitney U test showed a significant improvement in patients' satisfaction with nurses' education performance (P